Examining Ideational Meaning through the Transitivity System in Easy Arabic Podcast - Dainunah Lillahi Wahdah; Rinaldi Supriadi (Anaphora : Journal of Language, Literary, and Cultural Studies, 2026)
Listening skills in Arabic language learning have often emphasized comprehension outcomes rather than the process through which meaning is constructed through language. A similar tendency is also seen in Arabic-language podcasts, which are generally focused on improving listening skills, even though Arabic's root-based morphological system makes the linguistic encoding of meaning particularly rich and analytically significant. The way meaning is constructed through linguistic elements in speech, therefore, still rarely receives attention. Based on those conditions, this research aims to examine how the ideational function is realized in Arabic spoken discourse through the transitivity system employed in the Easy Arabic Podcast. Using a qualitative descriptive approach and content analysis within the framework of Systemic Functional Linguistics, the research analyzes 288 clauses from the Easy Arabic Podcast Episode 1 Listening transcript, focusing on process types, participants, and circumstances. The analysis identified six process types, with mental processes appearing most frequently with 92 clauses (31.94%), followed by material processes with 73 clauses (25.53%). These findings suggest that learning experiences are represented primarily through learners' cognitive engagement, complemented by concrete learning actions. Relational, verbal, behavioral, and existential processes further complement the realization of ideational meaning by configuring participants and circumstances. Accordingly, this study highlights that Arabic podcasts function not only as resources for listening practice but also as sites where ideational meanings are constructed through linguistic choices. By applying the transitivity system to Arabic digital spoken discourse, this research extends the application of Systemic Functional Linguistics beyond commonly examined written texts and formal speeches, providing insights into how learning experiences are represented through spoken Arabic.